JSPS-1 Overview of Foot and Mouth Disease Control in Thailand and Southeast Asia - Sith Premashthira (Hemera Zoa, 2018)
Foot and mouth disease (FMD) is endemic in many countries of Africa, the Middle East and Asia, and FMD-free countries face greater risk of incursions due to increased global movement and trade of livestock and animal [1]. In the Southeast Asia and China (SEACFMD) roadmap, the framework supports member countries to consider and improve their Progressive Control Pathway (PCP-FMD) stages (0-5) of FMD control and applies the FMD Official Control Programme recognized by OIE (World Organisation for Animal Health).